Efektifitas Kinerja Akuntansi Pemerintah Daerah Kabupaten Tegal - Eva Anggra Yunita (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2021)
Regional Government Accounting Performance is the output/result of a program that will be or has been achieved in connection with the use of regional budgets with measurable quality and quantity, regional capabilities can be measured by assessing the efficiency of services provided to the community. This study aims to determine the Effectiveness of Government Accounting Performance in the Regional Government of Tegal Regency in 2016-2019 based on the calculation of financial ratio analysis. This study uses a descriptive research method with a qualitative approach. The data used is secondary data in the form of the Regional Government Financial Report (LKPD) of Tegal Regency 2016-2019. The results of the research conducted showed that the Government Accounting Performance in the Tegal Regency Government in 2016-2019, (1) the PAD Effectiveness Ratio was categorized as quite effective with a value of 97.07%; (2) the Expenditure Efficiency Ratio is categorized as less efficient with a value of 91.04%; (3) The Expenditure Harmony Ratio still prioritizes the operational expenditure allocation of 78.38%, which is higher than the capital expenditure ratio of 21.38%.